Chikungunya infection in infants - Maria do Carmo Menezes Bezerra Duarte; Arino Faria de Oliveira Neto; Patrícia Gomes de Matos Bezerra; Lara Alves Cavalcanti; Vanessa Máximo de Brito Silva; Suelda Grasiela Alves Araújo de Abreu; Susana Farias Batista Leite; Nara Vasconcelos Cavalcanti
Abstract Introduction: the infection of chikungunya virus presents clinical manifestations variables, particularly in infants in which may present multiple cutaneous manifestations. Description: a case series study was carried out in an analytical character of 14 infants (>28 days to < 2 years old) admitted in a hospital between November 2015 and January 2016 with suspected case of chikungunya, by a specific IgM reactive serology. Patients positive for dengue fever, Zika virus, bacterial infections and other exanthematic diseases were excluded. Fever and cutaneous alterations were the most frequent clinical manifestations in 100% of the cases, followed by irritability (64.3%), vomits and arthralgia/arthritis in 35.7% each. Three children presented alterations in the cerebrospinal fluid compatible to meningitis. Anemia frequency was 85.7%. The median white blood cells count was 7.700/mm3 (2.600 to 20.300/mm3). High levels of aminotransferases were observed in three cases (230 to 450 U/L). Antibiotic therapy was indicated in 64.3% of the cases. Two infants needed opioid derivatives for analgesia while others took acetaminophen and/or dipyrone. Discussion: the study shows evident multi-systemic involvement of chikungunya infection in infants. The treatment is supportive, giving special attention to hydration, analgesia, skin care, and rational use of antibiotic therapy.